A comprehensive in silico and in vitro studies on quinizarin: a promising phytochemical derived from Rhizophora mucronata Lam. Issue 16 (2nd November 2022) - Sachithanandam, V.; Lalitha, P.; Parthiban, A.; Muthukumaran, Jayaraman; Jain, Monika; Misra, Ranjita; Mageswaran, T.; Sridhar, R.; Purvaja, R.; Ramesh, R.
Abstract: Mangrove plants are a great source of phytomedicines, since from the beginning of human civilization and the origin of traditional medicines. In the present study, ten different mangrove leaf methanolic extracts were screened for the type of phytochemicals followed by assessing antimicrobial, anti-oxidant and anti-cancer activities. The efficient methanolic crude extract of Rhizospora mucornata was further purified and characterized for the presence of the bioactive compound. Based on UV-visible spectroscopy, FTIR, NMR and HRMS analysis, the bioactive compound was 1, 4-dihydroanthraquinone; also termed as Quinizarin. This identified compound was potential in exhibiting antimicrobial, antioxidant, and cytotoxic activity. Quinizarin inhibited the growth of Bacillus cereus and Klebsiella aerogenes with minimum inhibitory concentration (MIC) of 0.78 and 1.5 mg/ml. The DPPH free radical scavenging assay revealed the maximum activity of 99.8% at the concentration of 200 µg/ml with an IC50 value of 12.67 ± 0.41 µg/ml. Cytotoxic assay against HeLa (cervical) and MDA-MB231(breast) cancer cell lines revealed IC50 values to be 4.60 ± 0.26 and 3.89 ± 0.15 µg/ml. Together the results of molecular docking and molecular dynamics simulation studies explained that Quinizarin molecule showed stronger binding affinity (−6.2 kcal/mol) and significant structural stability towards anti-apoptotic Bcl-2 protein. Thus, the study put forth the promising role of the natural molecule - Quinizarin isolated from R. mucornata in the formulation of therapeutic drugs against bacterial infections and cancer. Communicated by Ramaswamy H. Sarma